Dielectric Properties and Substantiation of Electromagnetic Technologies for Oil Sludge Processing - Abdeev, Eldar Rinatovich; Fatykhov, Minikhan Abuzarovich; Saitov, Rail Idiatovich; Abdeev, Rinat Gazizyanovich; Fatykhov, Lenart Minnehanovich (KnE Materials Science, 2020)
In the process of reception, storage and preparation of oil for processing, significant volumes of oil-containing sludge are formed, which are not only a source of pollution, but also a valuable hydrocarbon feedstock. Long-term storage of oil with water, contact with atmospheric oxygen, and the presence of solid particles hydrophobized with asphalt-resinous and paraffinous substances contribute to the formation of “intermediate layers” in these sludges, which are ultra-stable oil-water emulsions. It is proposed to use the energy of the electromagnetic field of the high and microwave ranges when developing a technology for the destruction of oil-water emulsions. After analyzing the composition of the oil sludge, experimental studies were conducted of the dielectric loss tangenttgδδ of oil with the addition of sand and paraffin, depending on the frequency of electromagnetic oscillations in the range of 30 - 160 MHz and temperature in the range of 25 - 80 ∘ С using the cumeter method. Studies have shown that two technologies for the disposal of oil sludge are possible: HF and UHF methods. To assess the effectiveness of their application, it is necessary to conduct experimental studies of the dielectric properties of oil sludge. Keywords: oil sludge, oil sludge disposal,oil storage, oil-water emulsions, electromagnetic field